Effect of the Nipple-Excising Breast-Conserving Therapy in Female Breast Cancer: A Competing Risk Analysis and Propensity Score Matching Analysis of Results Based on the SEER Database - Shouyu Li; Shouyu Li; Yuting Zhao; Yuting Zhao; Lutong Yan; Lutong Yan; Zejian Yang; Zejian Yang; Pei Qiu; Pei Qiu; Heyan Chen; Heyan Chen; et al. (Frontiers in Oncology, 2022)
IntroductionDue to the lack of randomized controlled trial, the effectiveness and oncological safety of nipple-excising breast-conserving therapy (NE-BCT) for female breast cancer (FBC) remains unclear. We aimed to explore and investigate the prognostic value of NE-BCT versus nipple-sparing breast-conserving therapy (NS-BCT) for patients with early FBC.MethodsIn this cohort study, data between NE-BCT and NS-BCT groups of 276,661 patients diagnosed with tumor–node–metastasis (TNM) stage 0–III FBC from 1998 to 2015 were retrieved from the Surveillance, Epidemiology, and End Results database. Propensity score matching analysis, Kaplan–Meier, X-tile, Cox proportional hazards model, and competing risk model were performed to evaluate the effectiveness and oncological safety for patients in NE-BCT and NS-BCT groups.ResultsA total of 1,731 (0.63%) patients received NE-BCT (NE-BCT group) and 274,930 (99.37%) patients received NS-BCT (NS-BCT group); 44,070 subjects died after a median follow-up time of 77 months (ranging from 1 to 227 months). In the propensity score matching (PSM) cohort, NE-BCT was found to be an adversely independent prognostic factor affecting overall survival (OS) [hazard ratio (HR), 1.24; 95% CI, 1.06–1.45, p=0.0078]. Subjects in NE-BCT group had similar breast-cancer-specific survival (BCSS) (HR, 1.15; 95%CI, 0.88–1.52, p=0.30) and worse other-causes-specific death (OCSD) (HR, 1.217; 95%CI, 1.002–1.478, p=0.048<0.05) in comparison with those in the NS-BCT group.ConclusionsOur study demonstrated that the administration of NE-BCT is oncologically safe and reliable and can be widely recommended in clinics for women with non-metastatic breast cancer.